STAT6 Upregulates NRP1 Expression in Endothelial Cells and Promotes Angiogenesis - Gao, Peng; Ren, Guanghui; Liang, Jiangjiu; Liu, Ju (Frontiers in Oncology, 2022)
The role of signal transducer and activator of transcription 6 (STAT6) in tumor growth has been widely recognized. However, its effects on the regulation of angiogenesis remain unclear. In this study, we found that STAT6 promoted angiogenesis, possibly by increasing the expression of neuropilin-1 (NRP1) in endothelial cells (ECs). Both STAT6 inhibitor (AS1517499) and STAT6 siRNA reduced EC proliferation, migration, and tube-formation, accompanied by downregulation of NRP1, an angiogenesis regulator. Furthermore, IL-13 induced activation of STAT6 and then increased NRP1 expression in ECs. IL-13-induced EC migration and tube formation were inhibited by NRP1 siRNA. Luciferase assay and chromatin immunoprecipitation assay demonstrated that STAT6 could directly bind to human NRP1 promoter and increase the promoter activity. In tumor xenograft models, inhibition of STAT6 reduced xenograft growth, tumor angiogenesis, and NRP1 expression in vivo. Overall, these results clarified the novel mechanism by which STAT6 regulates angiogenesis, and suggested that STAT6 may be a potential target for anti-angiogenesis therapy.